The criticism of governamental reason in Michel Foucault - Senellart, Michel (Tempo Social, 1995)
The article examines modern criticism of governamental reason which is focused by Foucault under two main aspects. First he analyses the concept of critique based on his own interpretation of Kant´s work, articulated  with an "ontology of the present". Besides  this, Foucault analyses the place ocuppied by liberalism in this critical procedure. Thus the article intends to show that Foucault´s criticism escapes from the imputation of reformism.